1991
DOI: 10.1002/ssu.2980070610
|View full text |Cite
|
Sign up to set email alerts
|

Type‐oriented therapy for gastric cancer effective for lymph node metastasis: Management of lymph node metastasis using activated carbon particles adsorbing an anticancer agent

Abstract: Activated carbon particles are taken selectively up by lymphatics when injected into the tissues and visualize regional lymph nodes colored black. Furthermore, carbon particles adsorb a large amount of the anticancer agent mitomycin C (MMC) on their surface and release the drug reversibly. Using these properties of activated carbon particles, we have applied it for lymph node dissection and chemotherapy of lymph node metastasis. After injection of carbon particles, regional lymph nodes of the stomach were foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 5 publications
1
17
0
1
Order By: Relevance
“…Lymphatic flow around the stomach was well investigated by Takahashi et al using activated carbon particles, which flow through the lymphatic vessels [19]. They reported that activated carbon particles injected into the wall of the upper portion of the greater curvature of the stomach flowed to the splenic hilar nodes.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphatic flow around the stomach was well investigated by Takahashi et al using activated carbon particles, which flow through the lymphatic vessels [19]. They reported that activated carbon particles injected into the wall of the upper portion of the greater curvature of the stomach flowed to the splenic hilar nodes.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphatic flow around the upper portion of the greater curvature of the stomach has been reported, toward the nodes around the splenic hilus and splenic artery (Takahashi et al, 1991). Yoshino et al have reported that spread of carcinoma is often to the lymph nodes around the splenic hilus and splenic artery when the primary tumour is located along the greater curvature of the upper third of the stomach (Yoshino et al, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Anatomy [10,25,27,33] and physiology [9,28,32,36] studies conducted on the gastric lymphatic drainage identified different pathways depending on the stomach's regions. Upper third lymphatic vessels run along left gastric artery, posterior gastric artery, and splenic artery, whereas the lower third has lymphatic vessels accompanying common hepatic artery and superior mesenteric artery.…”
Section: Introductionmentioning
confidence: 99%